Fetal primary pleural effusions: Prenatal diagnosis and management. (July 2019) - Abbasi, Nimrah; Ryan, Greg
Abstract: Fetal pleural effusions can be associated with significant perinatal morbidity and mortality. When diagnosed antenatally, referral to a tertiary fetal medicine center is recommended for a detailed ultrasound evaluation for additional structural abnormalities or features suggestive of congenital infections or fetal anemia. The effusions should be characterized as unilateral or bilateral, and presence of hydrops and/or mediastinal shift should be documented. Additional testing should include fetal echocardiography, maternal testing for blood group and screen, hemoglobinopathies, and congenital infections. Invasive genetic testing is recommended with infectious testing on amniotic or pleural fluid. Pleuroamniotic shunting is recommended for large primary pleural effusions with significant mediastinal shift or hydrops, as several large series have demonstrated improvement in perinatal survival, particularly in hydropic fetuses. Delivery should occur in a tertiary care center with neonatal expertise, and infants should be followed up long-term for respiratory and neurodevelopmental outcomes. Highlights: Fetal pleural effusions are associated with perinatal morbidity and mortality. Associated structural and genetic abnormalities should be excluded. Fetal chest shunts should be considered with large primary pleural effusions with significant mediastinal shift or hydrops.